2016
DOI: 10.1590/s0100-736x2016001200003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison phenotypic and genotypic identification of Staphylococcus species isolated from bovine mastitis

Abstract: In addition to Staphylococcus aureus nowadays other coagulase-positive staphylococci (CoPS) and coagulase-negative staphylococci (CoNS), earlier considered of minor importance, are now accepted as relevant pathogens for humans and animals. The involvement of these microorganisms in bovine mastitis etiology and the possibility their transmission through milk to humans justify the requirement of developing reliable methods for identification of the most frequent species among them. The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In Brazil, others authors found similar frequencies, ranging from 8.3% to 57.8% (COSTA KREWER et al, 2015;MARTINS et al, 2010;MELLO et al, 2012;LAFFRANCHI et al, 2001;OLIVEIRA et al, 2011). Besides S. aureus, other species of Staphylococcus that were earlier considered of minor importance are now accepted as relevant human and animal pathogens (GUIMARÃES et al, 2016). In the present study, four species of coagulasenegative staphylococci were identified: S. haemolyticus, S. epidermidis, S. pasteuri and S. xylosus, which were previously detected in mastitis milk samples (FREY et al, 2013;GUIMARÃES et al, 2016;SOARES et al, 2012;XU et al, 2015).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…In Brazil, others authors found similar frequencies, ranging from 8.3% to 57.8% (COSTA KREWER et al, 2015;MARTINS et al, 2010;MELLO et al, 2012;LAFFRANCHI et al, 2001;OLIVEIRA et al, 2011). Besides S. aureus, other species of Staphylococcus that were earlier considered of minor importance are now accepted as relevant human and animal pathogens (GUIMARÃES et al, 2016). In the present study, four species of coagulasenegative staphylococci were identified: S. haemolyticus, S. epidermidis, S. pasteuri and S. xylosus, which were previously detected in mastitis milk samples (FREY et al, 2013;GUIMARÃES et al, 2016;SOARES et al, 2012;XU et al, 2015).…”
Section: Resultsmentioning
confidence: 49%
“…Besides S. aureus, other species of Staphylococcus that were earlier considered of minor importance are now accepted as relevant human and animal pathogens (GUIMARÃES et al, 2016). In the present study, four species of coagulasenegative staphylococci were identified: S. haemolyticus, S. epidermidis, S. pasteuri and S. xylosus, which were previously detected in mastitis milk samples (FREY et al, 2013;GUIMARÃES et al, 2016;SOARES et al, 2012;XU et al, 2015). The results obtained reinforce the importance of these pathogens as mastitis causing agents in dairy herds of the Midwest region of Santa Catarina State, having a direct implication for infection control measures, since the correct identification of the etiological agent is fundamental to establishing appropriate prevention and control measures (HENNEKINNE et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…[32] reported that 3.8% of sea fish were positive for S. pasteuri . Another investigation in Brazilian dairy herds using milk samples from bovine mastitis cases reported the incidence of S. pasteuri as 3.3% [10]. According to epidemiological analysis, Savini et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies regarding Staphylococcus pasteuri as a potential pathogen found in various environmental conditions. The spread of S. pasteuri in plant food environments and animals has been reported by several authors and their studies described that vegetables [7,8], and leafy vegetables, including perilla leaf, chicory, and lettuce from local markets in South Korea [8], pig farms in the Netherlands [9], and bovine mastitis from Brazilian dairy herds [10] were contaminated or caused by S. pasteuri . In our previous investigation of cellulolytic Enterobacte r [11], and cellulolytic Bacillu s [12], both bacteria were found in the rumen of Aceh cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying S. aureus can use phenotypic and genotypic methods. Phenotypic methods include the culture method, followed by Gram staining, fermentation, catalase, and coagulase [10,11]. Genotypic methods include comparative methods based on standard band electrophoresis, genome characterization, and sequencing methods.…”
Section: Introductionmentioning
confidence: 99%